Manganese(II) and zinc(II) complexes of 4-phenyl(2-methoxybenzoyl)-3-thiosemicarbazide: Synthesis, spectral, structural characterization, thermal behavior and DFT study - Singh, Sanjay (Elsevier, 2014)
The ligand 4-phenyl(2-methoxybenzoyl)-3-thiosemicarbazide (Hpmt), forms isostructural [Mn(pmt)2(o-phen)] (1) and [Zn(pmt)2(o-phen) ] (2) complexes containing o-phen as coligand which have been characterized by analytical, spectroscopic (IR, UV-Vis, NMR), magnetic susceptibility, TGA and single crystal X-ray data. Both complexes crystallize in monoclinic systems with the space group P2/n. The complexes have distorted octahedral geometry around the metal center. The ligand in the complexes is coordinated through the deprotonated hydrazinic nitrogen and carbonyl oxygen. The hydrazinic nitrogen coordinates with a shorter M-N distance than the o-phen nitrogen and bond lengths in the chelate ring systems are intermediate between single and double bond distances, suggesting considerable delocalization of charge. There is a good agreement between the geometrical parameters obtained by X-ray crystallography to those generated by DFT method. The thermal degradations of complexes 1 and 2 have been investigated by thermogravimetric analyses which indicate that the final residues left are Mn(NCO)2 and Zn(NCSNH) 2. The small HOMO-LUMO energy gap suggests low excitation energy for the complexes.
Only IISERM authors are available in the record.
Keywords: DFT; Thiosemicarbazide; Mn(II) and Zn(II) complexes; Crystal structure; Supramolecular architecture; TGA